PENGARUH STRUKTUR KEPEMILIKAN, UKURAN PERUSAHAAN, DAN CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Reviani, Dinni; Sudantoko, Djoko (PRESTASI, 2012)
This study aimstoexamine the effect ofownership structure, firm size, andcorporate governanceonearningsmanagement. Goodcorporate governanceis representedbyan independent commissionersâs composition, audit quality, and theauditcommittee.This research use library research methods and documentation.The data used are secondary data obtained from the site of BEI www.idx.co.id, BEI UNDIP Corner, and the Indonesian Capital Market Directory (ICMD) in the form of financial statements and annual reports from 2008-2010 in the manufacturing sector industrial companies which are listed on Indonesia Stock Exchange. The samples used were 24 companies in the manufacturing category in the period 2008-2010 through a purposive sampling method. The analysis method of this research using multiple regression.Based on the result of study concluced that the variable independent commissionersâs composition and the presence of audit committee have a negative and significant effect on earning management. These result indicated the significance value of the independen commissioner are 0.025, and the significance value of audit committee are 0.001. These result mean that the independent commissionersâs composition and the presence of audit committee being able to reduce earning management. While the ownership structure variables with significance value 0.769, the size of the company with significance value 0.241, and the quality audit with significance value 0.443 showed no significant effect on earning management.Keywords: Ownership structure, size of firms, Corporate Governance, independent commissioners audit committee, audit quality, earnings management